(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Tribal migration is a significant phenomenon driven by various socio-economic factors, including poverty, lack of opportunities, and environmental vulnerabilities. The study analyzes the trends, patterns, and factors influencing migration, highlighting the complexities of tribal migration in the region. Using census data and other secondary sources, the study reveals that rural-to-rural migration is the most dominant stream, with marriage being the primary reason for female migration. The study's findings have implications for policymakers and development programs aimed at promoting sustainable development and improving the well-being of tribal communities.